The Narrative And Collectivity Of The Deradicalization Movement Regarding Terror Actions In Indonesia: A Twitter Analysis - Tawakkal Baharuddin; Rossi Maunofa Widayat; Zuly Qodir; Hasse Jubba (Faculty of Social and Political Sciences, Universitas Diponegoro, 2021)
This study is based on the events of acts of terrorism and the finding of radicalization efforts in Indonesia. This situation requires a response from many parties, including civil society, that is more participatory in supporting deradicalization efforts. This study aims to analyze the role of social media in influencing the narrative and interest of community collectivities in the deradicalization movement in Indonesia. The method used is quantitative discourse analysis. The data source is social media Twitter, with analysis tools using Nvivo 12 Plus. The study findings explain that Twitter social media can be an alternative in forming participatory, educative, and preventive narratives against deradicalization efforts in Indonesia. The use of social media Twitter can also influence the community's collective interest to get involved in opposing radicalism, whether online or in public space. The results of this research is that deradicalization efforts can also be carried out by utilizing social media, especially by maximizing hashtag and meme features. This finding is an essential argument that deradicalization efforts cannot be carried out with the same approach as shown by radicalism, in that deradicalization is not carried out with arrogance or violence but with a more educative participatory approach. This approach maximizes the potential of social media, which has proven to be more accommodating to reaching the wider community and is more participatory. The substance of this study is seen as a recommendation for maximizing the deradicalization movement in countering radicalism in Indonesia. The limitations of this study are in the research method, which only analyzes specific data sources, so further research is needed that can utilize data sources, especially in exploring data sources from other social media platforms.